Rapid determination of lead in progressive hair dye lotion by spot test/diffuse reflectance spectroscopy with a paper platform - Luiz, Vitor H. M. [UNESP]; Saraiva, Lívia M. [UNESP]; Martins, Ângela P. [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena R. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2015)
A simple, inexpensive, and clean methodology employing a combined spot test/diffuse reflectance spectroscopy procedure was developed and applied for the quality control analysis of lead in hair dyes, using a filter paper platform. The method is based on the complexation reaction of lead, present in a pH 2.8 buffer medium containing tartaric acid and sodium and potassium tartrate, with sodium rhodizonate (ROD) in an aqueous medium containing sodium dodecyl sulfate (SDS) surfactant, yielding a colored compound on the surface of a filter paper. The concentrations of ROD and SDS were optimized using experimental design. The linear range obtained for reflectometric measurements carried out at 545 nm was 4.70-140 mg L-1 of lead (R = 0.998), and the limits of detection and quantification were 1.12 and 3.75 mg L-1 , respectively. The proposed method was successfully applied to the analysis of lead in progressive hair dyes.
Keywords: Diffuse reflectance spectroscopy; Lead; Progressive hair dye; Spot test